Modernization of the load gripping device for forestry industry - A. N. Korolevskikh; O. A. Dvinskaya; E. A. Bogdanova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article proposes to install toothed plates on the contact surfaces of a foreign-made friction-clamping load-gripping device. The modernization of the friction-clamping load-gripping device is designed to use the device when moving goods from wood. The need for modernization is substantiated. The parameters of the gear plate are determined. The reliability of the upgraded friction-clamping loadgripping device is estimated. The article will be useful to engineers and researchers working on reverse engineering of foreign-made industrial equipment.